2002
DOI: 10.1037/0882-7974.17.2.236
|View full text |Cite
|
Sign up to set email alerts
|

College-educated women's personality development in adulthood: Perceptions and age differences.

Abstract: Adulthood encompasses a large time span and includes a series of psychosocial challenges (E. H. Erikson, 1950). Five aspects of personality (identity certainty, confident power, concern with aging, generativity, and personal distress) were assessed in a cross-sectional study of college-educated women who at the time of data collection were young adults (age: M = 26 years), middle-aged adults (age: M = 46 years), or older adults (age: M = 66 years). Respondents rated each personality domain for how true it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 41 publications
8
52
1
5
Order By: Relevance
“…Por ejemplo, tras incrementarse en la transición de la juventud a la mediana edad, el interés y las actividades generativas en general se mantienen en la vejez, tanto cuando se comparan trasversalmente diversos grupos de edad (Sheldon y Kasser, 2001;Zucker, Ostrove, y Stewart, 2002) como cuando las personas evalúan, retrospectivamente, la generatividad en diferentes momentos de su vida (Miner-Rubino, Winter, y Stewart, 2004). Así, la generatividad parece estar detrás de las contribuciones de los mayores tanto en ámbitos familiares como comunitarios (Kleiber y Nimrod, 2008;Thiele y Welan, 2008;Warburton y Gooch, 2007).…”
Section: La Generatividad En La Vejezunclassified
“…Por ejemplo, tras incrementarse en la transición de la juventud a la mediana edad, el interés y las actividades generativas en general se mantienen en la vejez, tanto cuando se comparan trasversalmente diversos grupos de edad (Sheldon y Kasser, 2001;Zucker, Ostrove, y Stewart, 2002) como cuando las personas evalúan, retrospectivamente, la generatividad en diferentes momentos de su vida (Miner-Rubino, Winter, y Stewart, 2004). Así, la generatividad parece estar detrás de las contribuciones de los mayores tanto en ámbitos familiares como comunitarios (Kleiber y Nimrod, 2008;Thiele y Welan, 2008;Warburton y Gooch, 2007).…”
Section: La Generatividad En La Vejezunclassified
“…Roberts, Caspi, and Moffitt (2001) linked personality change to work experience. Zucker, Ostrove, and Stewart (2002) discussed "ways in which women's adult development may have been shaped by experiences particular to both gender and birth cohort" (p. 236). Roberts, Wood, and Smith (2005) held that a driving mechanism of personality development is psychological investment in agegraded social roles.…”
Section: Interpreting Normative Age Changesmentioning
confidence: 99%
“…As did Stewart et al (2001) and Zucker et al (2002), we asked individuals to describe their feelings associated with aging both retrospectively (for their 40s and 20s) and concurrently (for their 60s-their current age). Thus, similar to previous work, this study relies on retrospective accounts for much of the data.…”
Section: Retrospective Accounts Of Agingmentioning
confidence: 99%
“…For example, Stewart, Ostrove, and Helson (2001) and Zucker, Ostrove, and Stewart (2002) found that college-educated women report feeling more certain about their identity, confident, powerful, and generative in midlife compared to earlier ages. Gender and social class may influence how individuals experience subjective aspects of aging (Cameron, 1970(Cameron, , 1973Gatz & Karel, 1993;Lachman, 1986;Ryff, 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation